GOOD GOVERNANCE UNIVERSITY; STRATEGIC MANAGEMENT APPLICATION BASED ON ISO 21001: 2018 - Luluk Indarti; Akmal Mundiri; Nofi Ferandita (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to analyze the implementation of strategic management based on ISO 21001-2018 in realizing superior Islamic boarding school-based university governance. This research uses a qualitative approach with the type of case study. The results show that strategic management based on ISO 21001-2018 is carried out through quality planning, control, and quality improvement. In quality planning, the quality control work unit and stakeholders formulate and prepare higher education governance plans according to ISO 21001: 2018 standards. In the quality control process, universities establish requirements and recommendations for design and quality assessment. Meanwhile, universities carry out continuous quality improvement by evaluating improvements that focus on Lean and Six Sigma techniques at the quality improvement stage. This research has implications for the importance of quality orientation carried out by higher education institutions in order to create public trust and customer loyalty.